(untitled) (The Pakistan Development Review, 1985)
Any system of ideas which underlies economic policy recommendations needs to be made explicit so that its doctrinal premise may be examined and debated. Section I of this paper, therefore, explicitly states the philosophical under -pinning of this study. Section 2 presents the central energy problem in a general mathematical form whereas the solution of the specific energy problem for the Pakistani economy is presented in Section 3, in which policy guidelines for obtaining the desired solution have also been discussed. Finally, Section 4 briefly presents our concluding remarks.